Parameters of proper marketing strategy of selected home appliances in kolkata - Ghosh, Chinmoy (International research journal of management, IT and social sciences, 2016)
Marketing strategies always chalk out in a specific manner, depending on that the companies can achieve their goal. This paper examined that the combination of five parameters (quality of material, brand, referral system, communication, niche market) create a structured marketing strategy, which will generate us a new model.